Cooperative Skills Development of 4–5 Year Olds through Bakiak Game: Perkembangan Keterampilan Kerja Sama Anak Usia 4–5 Tahun Melalui Permainan Bakiak - Modjo, Siti Hadija; Rocmah, Luluk Iffatur (Indonesian Journal of Islamic Studies, 2025)
General Background: Early childhood education plays a crucial role in shaping social-emotional development, including children’s ability to cooperate effectively with peers. Specific Background: In Al-Faqih Islamic Kindergarten, many 4–5-year-old children still showed individualistic tendencies and limited social interaction, indicating a lack of cooperative behavior. Knowledge Gap: Previous studies have explored traditional games to improve cooperation, yet few have examined structured, group-based bakiak games among early learners within an Islamic educational context. Aims: This study aimed to improve the cooperation ability of 4–5-year-old children through group-based bakiak games. Results: Using classroom action research with observation and reflection across two cycles, the findings revealed a progressive increase in cooperation ability from 36% (pre-cycle) to 86% (cycle II). Novelty: The study highlights the effectiveness of integrating traditional physical games with cooperative learning principles in Islamic kindergarten settings. Implications: The bakiak game can serve as an engaging pedagogical tool that fosters teamwork, empathy, and social harmony in early childhood education. Highlights: Traditional bakiak game effectively fosters cooperation in young children. Integration of play and learning strengthens social-emotional growth. Applicable model for Islamic early education environments. Keywords: Cooperation, Bakiak Game, Early Childhood, Social Skills, Islamic Education